Slow Recovery of Weight Bearing After Stabilization of Long-Bone Fractures Using Elastic Stable Intramedullary Nails in Children. Issue 11 (March 2016) - Lardelli, Patrizia; Frech-Dörfler, Martina; Holland-Cunz, Stefan; Mayr, Johannes
Abstract : Abstract: Stabilization of diaphyseal long-bone fractures using elastic stable intramedullary nails (ESIN) in children promises early mobilization and rapid resumption of full weight bearing. We evaluated the duration of postoperative functional rehabilitation after ESIN, measured by the time from stabilization until first partial weight bearing, full weight bearing, and resumption of school sports. Fifty children with unstable, displaced fractures of the femur or lower leg treated with ESIN between 2002 and 2012 were included in this retrospective analysis. We classified fractures according to the pediatric comprehensive classification of fractures (PCCF). Thirty-five children sustained a femur fracture, and 15 children had a fracture of the lower leg or tibia. The surgeons in charge applied an additional plaster cast in 7 of 15 children who suffered a lower leg fracture. The postoperative time interval until full weight bearing in the group of children who had suffered transverse or short oblique femur fractures was significantly shorter (median: 4.4 weeks; range: 0.1–9.1 weeks) than that in the group who had sustained more complex fracture patterns (median: 6.8 weeks; range: 2.9–13.9 weeks; P = 0.04). Similarly, transverse and short oblique lower leg and tibia fractures required less time until full weight bearing (median: 4.1 weeks; range 2.7–6.0 weeks) than complex lower leg fractures (median: 6.1 weeks; range: 1.3–12.9 weeks; P = 0.04). ESIN proved fairly effective in restoring full weight bearing in transverse or short oblique fractures of the lower extremities but was less effective in complex fractures.